2012
DOI: 10.1073/pnas.1208075109
|View full text |Cite
|
Sign up to set email alerts
|

Protection from the acquisition of Staphylococcus aureus nasal carriage by cross-reactive antibody to a pneumococcal dehydrogenase

Abstract: Nasal colonization by Staphylococcus aureus is the major risk factor for disease and transmission. Epidemiological studies have reported a reduced risk of S. aureus carriage in immunocompetent but not in immunocompromised children colonized by Streptococcus pneumoniae. We investigate the hypothesis that the immune response to pneumococcal colonization affects S. aureus colonization. We demonstrate that pneumococcal colonization in mice inhibits subsequent S. aureus acquisition in an antibody-dependent manner a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 37 publications
0
36
0
Order By: Relevance
“…In Cryptococcus neoformans, a pathogenic yeast, PUT2 is required for the optimal production of major cryptococcal virulence factors, and in mice, infection with a ⌬PUT2 mutant was determined to be nonvirulent (96). Another study has shown that the immune response underlying pneumococcal colonization affects Staphylococcus aureus colonization and identified S. aureus P5CDH as a target in a cross-reactive antibody response (97). In trypanosomatids, the participation of enzymes with pivotal roles beyond their canonical metabolic functions has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In Cryptococcus neoformans, a pathogenic yeast, PUT2 is required for the optimal production of major cryptococcal virulence factors, and in mice, infection with a ⌬PUT2 mutant was determined to be nonvirulent (96). Another study has shown that the immune response underlying pneumococcal colonization affects Staphylococcus aureus colonization and identified S. aureus P5CDH as a target in a cross-reactive antibody response (97). In trypanosomatids, the participation of enzymes with pivotal roles beyond their canonical metabolic functions has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…While the HIV studies may suggest that T-cell immune response plays a role in the interference, Lijek et al demonstrated in an in vivo murine model that S. pneumoniae colonization inhibits subsequent S. aureus acquisition in an antibody-dependent manner, via cross-reactive antibodies targeting conserved dehydrogenases, 1-pyroline-5-carboxylate dehydrogenase (P5CDH) of S. aureus and a putative S. pneumoniae dehydrogenase: SP_1119. 66 Yet, these antibodies have not been found in humans. In addition, other studies did not find correlations between levels of particular S. aureus or S. pneumoniae antibodies and rates of S. aureus colonization.…”
mentioning
confidence: 99%
“…Therefore, direct antagonism mediated by H 2 O 2 is an unlikely reason for their antagonism. Rather, the antibody response generated during S. pneumoniae infection, although ineffective in restricting this pathogen itself, is effective in providing cross-protection against S. aureus (71,72).…”
mentioning
confidence: 99%